The orchard [large type] - Lewis, Beverly, 1949- (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"For generations, Ellie Hostetler's family has tended their orchard, a tradition her twin brother, Evan, will someday continue. But when Evan is drafted for the Vietnam War, the family is shocked to learn he has not sought conscientious objector status. Can Ellie, with the support of a new beau, find the courage to face a future unlike the one she imagined?"--Amazon.com.